Epilepsy, Headache, and Quality of Life after Resection of Cerebral Arteriovenous Malformations - Rohn, Benjamin; Haenggi, Daniel; Etminan, Nima; Kunz, Mathias; Turowski, Bernd; Steiger, Hans-Jakob (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background In ruptured and unruptured arteriovenous malformations (AVMs), bleeding and re-bleeding rate and efficacy of microsurgical, endovascular, and radiosurgical treatment to prevent hemorrhage are well known. Uncertainty exists concerning the benefit of therapy with regard to headache, epilepsy, and quality of life (QoL) in unruptured AVMs. The objective of the present study was to gain long-term follow-up information after microsurgical AVM resection, in particular with regard to epilepsy, headache, and QoL.Methods A series of 110 patients with cerebral AVM, surgically treated between 1994 and 2009, were analyzed. Epidemiological, sociodemographic, and disease-related characteristics were extracted from the patient records. A detailed follow-up interview was possible with 51 patients after a median of 7 ± 5 years after surgery. A structured telephone interview using the Short Form (SF)-36 for QoL assessment was performed. In addition, specific questions regarding epilepsy and seizure outcome as well as independence and professional activity were asked.Results Hemorrhage led to hospital admission in 58.2% patients; 35.5% were admitted with epileptic seizures and 24.5% of patients reported chronic headaches. On the Spetzler-Martin scale, 26.0% were grade 1, 38% grade 2, 25% grade 3, and 11% grade 4. Preoperative embolization was performed in 43.6%. Treatment-associated new neurological deficits at the time of discharge from the hospital occurred in 25.5%. At the time of follow-up, 94.2% of the patients were completely independent (Barthel index of 100). 64.7% of the patients with preoperative epilepsy were free of disabling seizures or rarely have disabling seizures (Engel class 1 and 2), 16.7% reported no significant change, and 17.6% reported worsening. A total of 17.6% patients in whom epilepsy was not known at the time of AVM treatment reported new seizures after therapy, all but one had hemorrhage. 38.5% of patients with preoperative chronic headache reported improvement, 53.8% no change, and 7.7% deterioration. Regarding SF-36 QoL scores, a statistically significant difference from the age-matched German norm values was found in the dimensions Bodily Pain (p = 0.03) and Emotional Role Function (p = 0.04). There was a trend for lower physical and mental sum scores in patients undergoing emergency surgery.Conclusions SF-36–based QoL scores after treatment of AVM differ little from the age-matched German averages. The long-term results regarding chronic epilepsy and chronic headache need further analysis.
Keywords: cerebral arteriovenous malformation; quality of life; epilepsy; headache; SF-36